Johannine Christology and the early Church - Pollard, T. (Cambridge University Press, 1970)
Professor Pollard attempts to show how the early Church interpreted the Gospel of John and its witness to the person of Christ. The two paradoxes implicit in John's theology - the distinction between the Father and the Son in the unity of the Godhead, and the divinity and humanity of Jesus Christ - were developed in varying ways and the resultant heresies arose from attempts to deny one element or the other in each paradox. In their refutation of the heresies, on the other hand, the Fathers struggled to keep both elements of the paradoxes in equipoise. The different traditions came into conflict in the controversy which raged around the figure of Arius and his supporters in the fourth century, of which the climax came in the debate about the views of Marcellus of Ancyra.